2010
DOI: 10.1073/pnas.1001827107
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic drug susceptibility associated SNPs are enriched in expression quantitative trait loci

Abstract: Pharmacogenomics has employed candidate gene studies and, more recently, genome-wide association studies (GWAS) in efforts to identify loci associated with drug response and/or toxicity. The advantage of GWAS is the simultaneous, unbiased testing of millions of SNPs; the challenge is that functional information is absent for the vast majority of loci that are implicated. In the present study, we systematically evaluated SNPs associated with chemotherapeutic agent-induced cytotoxicity for six different anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 34 publications
1
109
2
1
Order By: Relevance
“…37 This model-free approach to gene discovery has led to a greater pathophysiologic understanding of many disorders, although only small proportions of the total genetic variance have so far been explained, and many of the identified variants have not brought new biological understanding. 38 To address the latter concern, functional support for GWAS findings has been sought by determining their effects on gene expression (expression quantitative trait loci- eQTLs) and methylation level (methylation quantitative trait loci-mQTLs). 38 Top single nucleotide polymorphisms (SNPs) have also been examined for potential enrichment of eQTLs and mQTLs, compared to expected rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 This model-free approach to gene discovery has led to a greater pathophysiologic understanding of many disorders, although only small proportions of the total genetic variance have so far been explained, and many of the identified variants have not brought new biological understanding. 38 To address the latter concern, functional support for GWAS findings has been sought by determining their effects on gene expression (expression quantitative trait loci- eQTLs) and methylation level (methylation quantitative trait loci-mQTLs). 38 Top single nucleotide polymorphisms (SNPs) have also been examined for potential enrichment of eQTLs and mQTLs, compared to expected rates.…”
Section: Introductionmentioning
confidence: 99%
“…38 To address the latter concern, functional support for GWAS findings has been sought by determining their effects on gene expression (expression quantitative trait loci- eQTLs) and methylation level (methylation quantitative trait loci-mQTLs). 38 Top single nucleotide polymorphisms (SNPs) have also been examined for potential enrichment of eQTLs and mQTLs, compared to expected rates. Moreover, examination for over-representation of micro-RNA (miRNA) binding sites has also been adopted as an informative approach, 39 given the role of miRNA in regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although there was no evidence of systematic bias, there were no SNPs with P values lower than neutral expectation. However, previous work has shown the value in examining functional subsets of SNPs, specifically SNPs associated with expression levels of nearby genes [cis-expression quantitative trait loci (cis-eQTL)], to enhance discovery from GWAS (26)(27)(28). Doing so also makes biological sense, because SNPs that alter nearby gene expression are more likely to affect cellular function as well.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that SNPs associated with human traits and chemotherapeutic drug susceptibility are in general enriched for eQTLs (Cookson et al, 2009;Gamazon et al, 2010;Nicolae et al, 2010). Most studies have used eQTL data from the most accessible cell type, LCL, and it is not clear how good a proxy these are for human cells and tissues relevant to nonimmune-related disease, such as psychiatric traits or cancers (Choy et al, 2008;Nicolae et al, 2010).…”
Section: Introductionmentioning
confidence: 99%